Long-term positive and negative psychological late effects for parents of childhood cancer survivors: a systematic review. - Lisa Ljungman; Martin Cernvall; Helena Grönqvist; Brjánn Ljótsson; Gustaf Ljungman; Louise von Essen (PLoS ONE)
Increasing survival rates in childhood cancer have yielded a growing population of parents of childhood cancer survivors (CCSs). This systematic review compiles the literature on positive and negative long-term psychological late effects for parents of CCSs, reported at least five years after the child's diagnosis and/or two years after the end of the child's treatment. Systematic searches were made in the databases CINAHL, EMBASE, PsycINFO, and PubMed. Fifteen studies, published between 1988 and 2010, from 12 projects were included. Thirteen studies used quantitative methodology, one quantitative and qualitative methodology, and one qualitative methodology. A total of 1045 parents participated in the reviewed studies. Mean scores were within normal ranges for general psychological distress, coping, and family functioning. However, a substantial subgroup reported a clinical level of general psychological distress, and 21-44% reported a severe level of posttraumatic stress symptoms. Worry, disease-related thoughts and feelings, marital strains, as well as posttraumatic growth was reported. Several factors were associated with the long-term late effects, such as parents' maladaptive coping during earlier stages of the childs disease trajectory and children's current poor adjustment. Quality assessments of reviewed studies and clinical implications of findings are discussed and recommendations for future research are presented.